2022
DOI: 10.5897/ajb2022.17489
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of genetic diversity of local rice accessions cultivated in Guinea revealed by SNPs markers, and identification of markers associated with tolerance to iron toxicity

Abstract: Rice is the staple food in the Republic of Guinea. However, its production is seriously hampered by iron toxicity. The fight against this stress necessarily involves the search for tolerant or resistant varieties. The study aims to determine quantitative trait locus (QTL) associated with tolerance to iron toxicity and to identify genotypes tolerant or resistant to iron toxicity. Thus, 90 local rice accessions collected in two regions of Guinea with high iron toxicity were evaluated using 33,537 single nucleoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, Worede et al. (2013) used SSR markers to successfully group NERICA 3 and NERICA 4, upland accessions, into the Japonica cluster with Azucena, a tropical japonica (Laho et al., 2022; D. Wang et al., 2018). L. Barry et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Worede et al. (2013) used SSR markers to successfully group NERICA 3 and NERICA 4, upland accessions, into the Japonica cluster with Azucena, a tropical japonica (Laho et al., 2022; D. Wang et al., 2018). L. Barry et al.…”
Section: Resultsmentioning
confidence: 99%
“…This was confirmed by W. , where NER-ICA 1, 2, 8, and 9 were classified as tropical japonica and NERICA-L-1, -20 and, -27 as indica-1B, the subpopulation that includes modern cultivars of diverse origins. Furthermore, Worede et al (2013) used SSR markers to successfully group NERICA 3 and NERICA 4, upland accessions, into the Japonica cluster with Azucena, a tropical japonica (Laho et al, 2022;. L. Barry et al (2022) reported NERICA-L-19 clustered with IR64 and Bouake 189, which were identified as indica2 by D. .…”
Section: Crop Sciencementioning
confidence: 99%